2020
DOI: 10.3390/ani10061031
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrolyzed Insect Meals in Sea Trout Fingerling (Salmo trutta m. trutta) Diets on Growth Performance, Microbiota and Biochemical Blood Parameters

Abstract: The present study is the first introduction of hydrolyzed superworm meal in sea trout nutrition. It was conducted to evaluate the effects of inclusion in the diet of hydrolyzed insect meals as a partial replacement for fishmeal on growth performance, feed utilization, organosomatic indices, serum biochemical parameters, gut histomorphology, and microbiota composition of sea trout (Salmo trutta m. trutta). The experiment was performed on 225 sea trout fingerlings distributed into three groups (3 tanks/treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 99 publications
(119 reference statements)
11
41
0
Order By: Relevance
“…The data showed no major effects of FM substitution with TM meal on species richness and diversity of both gut mucosa-and skin mucus-associated bacteria. In line with our results, the inclusion of hydrolysed TM meal did not affect the total number of digesta-associated bacteria in sea trout (Salmo trutta m. trutta) [39]. In contrast, in the study of Józe ak et al [40], the total number of intestinal bacteria increased in rainbow trout fed a diet in which FM was partially replaced by TM in comparison to control sh that were fed a FM-based diet.…”
Section: Discussionsupporting
confidence: 90%
“…The data showed no major effects of FM substitution with TM meal on species richness and diversity of both gut mucosa-and skin mucus-associated bacteria. In line with our results, the inclusion of hydrolysed TM meal did not affect the total number of digesta-associated bacteria in sea trout (Salmo trutta m. trutta) [39]. In contrast, in the study of Józe ak et al [40], the total number of intestinal bacteria increased in rainbow trout fed a diet in which FM was partially replaced by TM in comparison to control sh that were fed a FM-based diet.…”
Section: Discussionsupporting
confidence: 90%
“…However, the fish did not grow well in this unique study showing adverse effect of dietary insects on fish microbiota (Xiang et al, 2019). Indeed, although dietary TM or ZM did not affect the richness of sea trout's microbiota, they significantly reduced the occurrence of potential pathogens (Mikołajczak et al, 2020). Moreover, several studies have shown that both HI and TM increased the gut microbiota diversity of rainbow trout (Antonopoulou et al, 2019;Huyben et al, 2019;Józefiak et al, 2019b).…”
Section: Fish and Crustaceans Gut Microbiotamentioning
confidence: 61%
“…In particular, Firmicutes lactic acid producing bacteria (LAB), often used as probiotics and known to improve mucosal activity and to produce antimicrobial bacteriocins, were more abundant in the intestines of rainbow trout and Siberian sturgeon fed with HI (Bruni et al, 2018;Huyben et al, 2019;Józefiak et al, 2019a,b, Terova et al, 2019. However, this was not the case of sea trout fed TM, where Lactobacillus counts reduced compared to FM-fed fish (Mikołajczak et al, 2020). Other commensal bacteria with antibacterial or antiviral activity (e.g.…”
Section: Fish and Crustaceans Gut Microbiotamentioning
confidence: 90%
See 1 more Smart Citation
“…The need to find innovative sources for food and feed production has led to an increased recognition of insects 2,27,28 . Currently, about 92% of the ~ 2000 edible insect species worldwide is wild harvested 29 .…”
Section: Discussionmentioning
confidence: 99%